Some Metabolic Aspects of Septic Encephalopathy: Clinical and Experimental Study - S. V. Palyanov; V. T. Dolgikh; A. K. Chernyshev; O. V. Korpacheva (Общая реаниматология)
The paper deals with the clinical and experimental studies of the pathogenetic factors underlying the development of septic encephalopathy in the presence of the systemic inflammatory response syndrome. Particular emphasis is laid on carbohydrate metabolic disturbances in the brain as one of the most important factor for neurons. The experimental section presents the age-related features of cerebral carbohydrate metabolism in the development of sepsis.